In vivo efficacy of humanized high dose meropenem and comparators against Pseudomonas aeruginosa isolates producing verona integron-encoded metallo-β-lactamase (VIM). Issue 6 (June 2016) - Ghazi, Islam M.; Crandon, Jared L.; Lesho, Emil P.; McGann, Patrick; Nicolau, David P.
Abstract: Introduction: We aimed to describe the in vivo efficacy of meropenem, in addition to cefepime and levofloxacin as comparators against VIM-producing Pseudomonas aeruginosa and compare the findings to our previous observations with Enterobacteriaceae . Methods: Eight clinical P. aeruginosa isolates with meropenem MICs from 4 to 512 mg/L were studied in a murine neutropenic thigh infection model. Animals were treated with doses of the antibiotics to simulate the human exposure of meropenem 2 g q8 h 30-min infusion, cefepime 2 g q8 h 30-min infusion and levofloxacin 500 mg q24 h. After 24 hours, the animals were euthanized and efficacy was calculated as the change in thigh bacterial density (log10 CFU) relative to the starting inoculum (0 h). Results: As expected, levofloxacin was ineffective against all isolates due to their resistant phenotype (8 to>64 mg/L). Cefepime also showed minimal activity against all isolates consistent with its failure to achieve pharmacodynamic target exposures due to high MICs of 32 to>512 mg/L. In the presence of low MICs (4 to 16 mg/L), the f T> MIC of meropenem was sufficiently high to result in CFU reductions. However, conflicting activity was noted for isolates with MICs = 128 mg/L that possessed the same enzymatic profile, suggesting that other mechanisms of resistance are responsible for driving CFU outcomes. No activity was noted for organisms with a meropenem MIC = 512 mg/L. Conclusion: Unlike previous observations with MBL-producing Enterobacteriaceae that showed discordance between in vitro resistance and in vivo efficacy in the murine infection model, we found that the efficacy of humanized cefepime and meropenem was generally concordant with the phenotypic profile of VIM-producing P. aeruginosa .